Pretreatment with PCSK9 inhibitor protects the brain against cardiac ischemia/reperfusion injury through a reduction of neuronal inflammation and amyloid beta aggregation - Nattayaporn Apaijai (2019)
© 2019 The Authors. Published on behalf of the American Heart Association, Inc., by Wiley. Background Cardiac ischemic/reperfusion (I/R) injury leads to brain damage. A new antihyperlipidemic drug is aimed at inhibitingPCSK9 (proprotein convertase subtilisin/kexin type 9), a molecule first identified in a neuronal apoptosis paradigm. Thus, thePCSK9 inhibitor (PCSK9i) may play a role in neuronal recovery following cardiac I/R insults. We hypothesize thatPCSK9i attenuates brain damage caused by cardiac I/R via diminishing microglial/astrocytic hyperactivation, β-amyloid aggregation, and loss of dendritic spine. Methods and Results Adult male rats were divided into 7 groups: (1) control (n=4); (2)PCSK9i without cardiac I/R (n=4); (3) sham (n=4); and cardiac I/R (n=40). Cardiac I/R rats were divided into 4 subgroups (n=10/subgroup): (1) vehicle; (2)PCSK9i (10μg/kg, IV) before ischemia; (3)PCSK9i during ischemia; and (4)PCSK9i at the onset of reperfusion. At the end of cardiac I/R protocol, brains were removed to determine microglial and astrocytic activities, β-amyloid aggravation, and dendritic spine density. The cardiac I/R led to the activation of the brain's innate immunity resulting in increasing Iba1 + microglia,GFAP + astrocytes, andCD11b + /CD45 +high cell numbers. However, CD11b + /CD45 +low cell numbers were decreased following cardiac I/R. In addition, cardiac I/R led to reduced dendritic spine density, and increased β-amyloid aggregation. Only the administration ofPCSK9i before ischemia effectively attenuated these deleterious effects on the brain following cardiac I/R.PCSK9i administration under the physiologic condition did not affect the aforementioned parameters. Conclusions Cardiac I/R injury activated microglial activity in the brain, leading to brain damage. Only the pretreatment withPCSK9i prevented dendritic spine loss via reduction of microglial activation and Aβ aggregation.